THE CORRELATION BETWEEN STUDENTS’ UNDERSTANDING IN WH- QUESTIONS AND THEIR SPEAKING ABILITY IN EXPRESSION OF ASKING AND GIVING OPINIONS OF THE EIGHTH YEAR STUDENTS OF SMP SWASTA HARAPAN BANGSA KUALA - Shely Perbina Br Sitepu; Ayu Indari (Serunai : Jurnal Ilmiah Ilmu Pendidikan, 2021)
This study was conducted by applying correlational study which aimed to find out whether the students’ understanding in WH-Questions significantly correlates to their speaking ability in expression of asking and giving opinions. The subject of the study was 36 students at the 2020/2021 eighth year students of SMP Swasta Harapan Bangsa Kuala. The essay test consisted of 20 items was used to obtain the data on the students’ understanding in WH-Questions and oral test to collect the data on their speaking ability in asking and giving opinions. Beside the instrument of essay test which was analyzed as valid by looking at that coefficient of tcounted (5.85) was greater than the ttable coefficient (1.69092) and also it was analyzed as reliable by looking at that coefficient of reliability (0.793) was greater than the rtable coefficient (0.2785); as well as through the technique of Pearson Product Moment correlation analysis that the correlation coefficient of 0.72 was located between 0.600 – 0.799. It means that the degree of the correlation was considered as high. From the table of this critical value for Pearson’s r, it was got that for the 0.05 significance level the critical value was 0.2785. The data showed that the value of correlation coefficient (0.72) was higher than the critical value from the table (0.2785). This means that there is significant correlation between students’ understanding in WH-Questions and their speaking ability in expression of asking and giving opinions. Therefore, the hypothesis of the study is accepted.